Honor in America? : Tocqueville on American enlightenment - Johnson, Laurie M. (Honor and obligation in liberal society., 2017)
This book analyzes Tocqueville's views on religion, family and gender roles, politics, relations with Native Americans, white southerners and slavery, and the military. It explores how these views can help form a uniquely American honor code, one that re-envisions aristocratic elements of honor within a modern democratic and capitalist society.